2008
DOI: 10.1002/jnr.21646
|View full text |Cite
|
Sign up to set email alerts
|

Adult human spinal cord harbors neural precursor cells that generate neurons and glial cells in vitro

Abstract: Adult human and rodent brains contain neural stem and progenitor cells, and the presence of neural stem cells in the adult rodent spinal cord has also been described. Here, using electron microscopy, expression of neural precursor cell markers, and cell culture, we investigated whether neural precursor cells are also present in adult human spinal cord. In well-preserved nonpathological post-mortem human adult spinal cord, nestin, Sox2, GFAP, CD15, Nkx6.1, and PSA-NCAM were found to be expressed heterogeneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 43 publications
8
108
1
Order By: Relevance
“…First, in contrast to mice, the central canal of the human spinal cord is often occluded (Dromard et al 2008), as previously reported by (Fuller and Burger 1997;Milhorat, Kotzen, and Anzil 1994), and the ependymal region appeared disorganized, with the frequent presence of rosettes or microcanals. Reminiscent of the reported difference between the SVZ in rodents and humans (Quinones-Hinojosa et al 2006), the human central canal is surrounded by a hypocellular region containing a high density of GFAP filaments and nerve fibers (Dromard et al 2008). Equally contrasting with rodents, a cluster of Nestin + subependymal cells was repeatedly observed in the ventral regions of cervical and lumbar spinal cords.…”
Section: Neural Precursor Cells In the Adult Human Spinal Cordsupporting
confidence: 57%
See 1 more Smart Citation
“…First, in contrast to mice, the central canal of the human spinal cord is often occluded (Dromard et al 2008), as previously reported by (Fuller and Burger 1997;Milhorat, Kotzen, and Anzil 1994), and the ependymal region appeared disorganized, with the frequent presence of rosettes or microcanals. Reminiscent of the reported difference between the SVZ in rodents and humans (Quinones-Hinojosa et al 2006), the human central canal is surrounded by a hypocellular region containing a high density of GFAP filaments and nerve fibers (Dromard et al 2008). Equally contrasting with rodents, a cluster of Nestin + subependymal cells was repeatedly observed in the ventral regions of cervical and lumbar spinal cords.…”
Section: Neural Precursor Cells In the Adult Human Spinal Cordsupporting
confidence: 57%
“…There are major differences between the rodent and primate brain, not only concerning size and organization but also for the cell diversity and SVZ organization. Consequently, we set out to explore the organization of the central canal region and the presence of neural stem cells in the adult human spinal cord (Dromard et al 2008). For this purpose, we used lumbar spinal cords from brain-dead organ-donor patients (24-70 years old) (Fig.…”
Section: Neural Precursor Cells In the Adult Human Spinal Cordmentioning
confidence: 99%
“…Cells removed from the ependymal regions of spinal cords from fresh autopsy tissue (organ transplant donors) differentiated into neurons and glia in vitro, 17,18 suggesting both a multipotent and a self-renewing capacity. Neurospheres formed from these cells expressed high levels of nestin, a marker of neural progenitor cells, and SOX2, a marker of neural stem cells, and displayed a morphology with long nestin-positive processes radially emanating from the neurospheres 18 in a manner reminiscent of tanycyte morphology.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,16 Endogenous NPC present in the adult human spinal cord have been isolated from fresh autopsy tissue, cultured, and shown to differentiate into neurons and glial cells in vitro. 17,18 One of the common markers for progenitor cells, nestin, is increased in the ependyma of human spinal cords from patients with multiple sclerosis, 19 amyotrophic lateral sclerosis (ALS), and spinal tumors, 20 and in hydrocephalic infants. 21 There are discrepancies in the reported antigenicity, development, location, and response of cells purported to be NPC in the spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation